Demineralized dentin characteristics after application of Mauli banana stem gel - Carabelly, Amy Nindia; Puspitasari, Dewi; Syahrina, Fitri; Wahyudi, Maman Diki; Salsabila Karno, Dhya Aurellia; Mohd-Said, Shahida (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Demineralization of dentin is a condition of dissolving minerals in peritubular dentin due to exposure to acids that release hydroxyapatite ions. To prevent dentin demineralization, a therapeutic agent that can inhibit the dissolution ability of hydroxyapatite ions is needed. One therapeutic agent that can be used is the Mauli banana (MB) stem gel. Purpose: To observe the characteristics of dentin demineralization after the use of MB stem extract gel. Method: Mandibular incisor bovine teeth were demineralized with lactic acid pH 4.5 for 72 hours and then treated with 25%; 37.5%; 50%; and 62.5% MB gel and Chlorhexidine 2% for one minute. All samples were soaked in artificial saliva with 1 mg/ml saliva of collagenase enzyme for 24 hours. The characteristic of dentin demineralization was observed by using scanning electron microscope/electron dispersive X-ray spectroscopy (SEM-EDX). Results: The SEM image in the control, Chlorhexidine, 25%; 37.5%; 50%; and 62.5% MB gel groups showed dentinal tubules of about 3.67–4.94 µm; 3.55–4 µm; 4.18–5.6 µm; 2.28–2.86 µm; 3.29–3.81 µm; and 2.42–3.17 µm in size. The EDX test found carbon (C), nitrogen (N), oxygen (O), sodium (Na), phosphorous (P), chlorine (Cl), and calcium (Ca) in all groups. The one-way Analysis of Variance (ANOVA) test results showed significant differences in the levels of C, N, O, Cl, and Ca between all groups, while the Na showed no significant differences. Conclusion: The MB can inhibit the demineralization of bovine dentin based on the decrease in the size of the dentinal tubules and increasing the C, O, P, and Ca.